2024
DOI: 10.3389/fpsyg.2024.1349880
|View full text |Cite
|
Sign up to set email alerts
|

Does physical activity influence health behavior, mental health, and psychological resilience under the moderating role of quality of life?

Ru Liu,
Rashid Menhas,
Zulkaif Ahmed Saqib

Abstract: BackgroundPhysical activity significantly influences health-related behaviors, encompassing physical and mental well-being. Physical activity has been linked to enhancing health behavior, mental health, and psychological resilience. The current study is based on participants who were active in physical activity to improve health and well-being.ObjectivesTo examine the influences of physical activity on health behavior, mental health, and psychological resilience, considering the moderating role of quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(114 reference statements)
1
1
0
Order By: Relevance
“…Some recent studies show similar results, as in the findings of Liu et al (2024), who reported that physical activity influences general health behaviors, which leads to an increase in well-being and mental health, ultimately affecting psychological resilience, as demonstrated in a conceptual model proposed.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Some recent studies show similar results, as in the findings of Liu et al (2024), who reported that physical activity influences general health behaviors, which leads to an increase in well-being and mental health, ultimately affecting psychological resilience, as demonstrated in a conceptual model proposed.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, we can see that in this aging process, maintaining mental and physical health through the practice of physical activity seems to be a great ally in preventing the development and/or progress of psychological and physical illnesses (Chapman et al, 2013;Liu et al, 2024) by increasing autonomy, including in daily life activities of the older adults (Rodrigues et al, 2016). Therefore, physical activity becomes a great ally in maintaining mental health, becoming a modifiable factor in the relationship with constant improvement in cognitive factors in successful aging (Liu et al, 2024;Moore et al, 2015;Rowe and Kahn, 1997;Vecchio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%